Sosialisasi Analisis Kualitas Lingkungan Berdasarkan Bioindikator yang ada di Lingkungan Sekitar - Ernawati, Ernawati; Rohyani, Immy Suci; Jupri, Ahmad; Isrowati, Isrowati; Rahayu, Rachmawati Noviana; Reda, Reda (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
A healthy and sustainable environment is critical for sustaining ecological balance and increasing human well-being. However, other human activities, such as industrialization, urbanization, and the use of chemicals in agriculture, can have a negative impact on the environment. As a result, the community requires an effective and simple way for integrating their surroundings. Bioindicator-based analysis is one approach of assessing environmental quality. Bioindicators are creatures whose presence, quantity, or physical condition can reflect the state of their surroundings. Plankton, macrozobenthos, moss, lichen, soil insects, and other microorganisms are examples of bioindicators. This community service project seeks to raise public awareness of the significance of bioindicators in environmental quality assessment, as well as how to identify the many types of bioindicators found in the surrounding environment and how to utilize them to assess air, soil, and air quality. The community service activity is divided into three stages: preparation (site survey and activity needs, permissions), implementation (socialization and poster exhibition), and assessment (participants completing questionnaires). The community service activity ran successfully. Throughout the socialization activities, all participants were engaged and eager. The material supplied was fresh to the participants and would be fascinating to examine further. Furthermore, participants were interested in attempting to determine environmental quality by observing the presence of bioindicators around them. Socialization activities were also able to instill in participants a sense of awareness and concern for environmental changes, prompting them to take an active role in sustaining the ecosystem in their surrounds.